OTERO, Hernán (2012). Historia de los franceses en la Argentina. Buenos Aires: Editorial Biblos, 387 p. - Lavallé, Bernard (Dirāsāt Hispānicas. Revista Tunecina de Estudios Hispánicos, 2014)
Reseña bibliográfica.